Splitting Tournaments - Edwin Leuven; Hessel Oosterbeek; Bas van der Klaauw (Institute for the Study of Labor (IZA), 2010)
In this paper we investigate how heterogeneous agents choose among tournaments with different prizes. We show that if the number of agents is sufficiently small, multiple equilibria can arise. Depending on how the prize money is split over the tournaments, these may include, for example, a perfect-sorting equilibrium in which high-ability agents compete in the high-prize tournament, while low-ability agents compete for the low prize. However, there are also equilibria in which agents follow a mixed strategy and there can be reverse sorting, i.e. low-ability agents are in the tournament with the high prize, while high-ability agents are in the low-prize tournament. We show that total effort always decreases compared to a single tournament. However, splitting the tournament may increase the effort of low-ability agents.
Keywords: D02; D04; 330; self-selection; tournament; heterogeneous agents; social planner; Glücksspiel; Entscheidung bei Unsicherheit; Gleichgewichtstheorie; Spieltheorie